Effectiveness of Botanical Pesticide from Keji Beling Leaves (Strobilanthes crispus) on Spinach Plants (Amaranthus tricolor L.) Against Pest Intensity - Wulandari, Desi; Listiana, Ika (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Crop failure in cultivated plants can be influenced by several factors, including pest attacks. Pest control in plants is often carried out using pesticides made from chemical compounds, which can have negative effects on health and the environment. One alternative to chemical pesticides is the use of botanical pesticides. This study aims to determine the effect of botanical pesticides made from keji beling leaves (Strobilanthes crispus) on the intensity of pest attacks on spinach plants (Amaranthus tricolor L.). The research was conducted using an experimental method from June to August 2024 in Kelapa Tujuh Village, South Kotabumi District, North Lampung Regency, Lampung Province, and at the Zoology Laboratory, Faculty of Science and Technology, Raden Intan State Islamic University, Lampung. The study used a Completely Randomized Design (CRD) with four treatments: applying botanical pesticides at concentrations of 25%, 50%, 75%, and 0% (control). Each treatment was repeated 16 times, resulting in 64 plant samples. The parameters studied included pest attack intensity, plant height, and root length. Data were analyzed using analysis of variance (ANOVA) and further tested with the Least Significant Difference (LSD) test at a 5% significance level to determine significant differences. Phytochemical screening tests revealed that keji beling leaf-based botanical pesticides contain alkaloids, saponins, and tannins. The results showed that applying botanical pesticides from keji beling leaves influenced all the parameters studied. The treatment with a 75% concentration was the most effective, resulting in the lowest leaf damage at only 10%, a plant height of 22.40 cm, and a root length of 13.47 cm. Based on these findings, keji beling leaf-based botanical pesticides have the potential to serve as an environmentally friendly alternative for pest control in spinach cultivation.